Effect of Pressure on Fabrty- Perot Interferometer Fringes Pattern. - Hussain, M.T.; Hatif, S.A.H.; Hadi, M.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A design and construction of Fabry -Perot Interometer system were achivcd to spcify and calculate wavelengths to the neart nanometers for spectroscopic research investigation, this accuracy required for as the refractive index is a function of pressure on the medium when the space between the two windows is keptn constant . He-Ne laser (632.8) nrn and the green laser (532) nm were used as coherent sources. Lasers of (632.8) & (532)nm respeCtively, were used as coherent sources. Results showed accuracy of (0.2)nm in determining the wavelength when (lOO) mm Hg difference in pressure was applied . The wavelength and the refractive index were calculated when prcesure was varied the rough Fabrt -Perot interferometer for bth wavelengths.